2012
DOI: 10.1002/htj.21013
|View full text |Cite
|
Sign up to set email alerts
|

MHD natural convection inside an inclined trapezoidal porous enclosure with internal heat generation or absorption subjected to isoflux heating

Abstract: A steady laminar two‐dimensional magneto‐hydrodynamic natural convection flow in an inclined trapezoidal enclosure filled with a fluid‐saturated porous medium is investigated numerically using a finite difference method. The left and right vertical sidewalls of the trapezoidal enclosure are maintained at a cold temperature. The horizontal top wall is considered adiabatic while the bottom wall is subjected to isoflux heating. A volumetric internal heat generation or absorption is embedded inside the trapezoidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Convergence criteria (10 −6 ) is chosen for all dependable variables and the value of (0.1) is used for the relaxation parameters the approach similar to Ref. [2]. It is found that a grid size (48 × 192) ensured a grid independent solution for the present study as shown in Table 1.…”
Section: Grid Testing and Validation Of The Numerical Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Convergence criteria (10 −6 ) is chosen for all dependable variables and the value of (0.1) is used for the relaxation parameters the approach similar to Ref. [2]. It is found that a grid size (48 × 192) ensured a grid independent solution for the present study as shown in Table 1.…”
Section: Grid Testing and Validation Of The Numerical Resultsmentioning
confidence: 99%
“…Governing equations were solved in a generalized orthogonal coordinate system using high-order compact finite difference method. Effects of geometrical parameters such as eccentricity, ratio axis length of elliptic enclosure as well as cylinder were investigated on heat transfer rate at a constant Ra = 100 and hydraulic-radius ratio (2). They concluded that the rate of heat transfer losses could be minimized by a proper choice of the elliptic shape of a concentric annulus which could be further enhanced if the geometry was made eccentric.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Oztop et al [6] considered an open porous tilted square and concluded that the inclination angle is the most important control parameter for the evolution of the flow and the convection. Kherief et al [7] considered an inclined rectangular cavity filled with mercury in the presence of a magnetic field which reduce significantly the average Nusselt number, as well as Hussein et al [8] who's considered a range of angles between 0° and 90° to study the magnetohydrodynamic natural convection in an inclined trapezoidal enclosure filled with a fluid-saturated porous medium. Some authors have chosen to add partitions in different position on the cavities; for example, Mamou et al [9] studied the heat transfer for different inclinations and partition's number and thickness.…”
Section: Introductionmentioning
confidence: 99%